Detection of chlorinated organic pollutants with an integrated screen-printed electrochemical sensor based on a carbon nanocomposite derived from bread waste. (20th December 2022) - Duan, Wenchao; Baez-Gaxiola, Martha Raquel; Gich, Martí; Fernández-Sánchez, César
Highlights: A sample-to-result sensor to monitor halogenated compounds in waters. Bread waste upcycled into functional Ag-doped carbon electrode material. Potential on-site analysis of halogenated compounds with an electrochemical device. Simple, sustainable, environmentally and user-friendly sensor configuration. Low-cost sensor fabrication to be potential for industrial mass production. Abstract: Halogenated organic compounds are ubiquitous in water bodies due to anthropogenic activities and some of them pose a real threat to the aquatic environment and human health. That is the case of artificial sweeteners such as sucralose and haloacetic acid disinfection byproducts such as trichloroacetic acid (TCA), classified as contaminants of emerging concern. This motivates the search for rapid, cost-effective and easy-to-use analytical tools that could be deployed to facilitate the analysis of organohalide pollutants and aid in accurately monitoring water quality. This work explores the rapid detection of sucralose and TCA using a very simple miniaturized sample-to-result integrated electrochemical sensor. The device incorporates a screen-printed three-electrode electrochemical cell (SPE) where the working electrode is made of a nanocomposite of Ag nanoparticles and porous C (Ag/C). The material is prepared from bread waste, in an attempt to add value to one of the largest fractions of food leftovers and thus contribute to the sustainable circular economy. The electrochemical process behind the sensor analytical performance is initially evaluated using free Cl − ions in solution and then, the sensor is used to analyze the mentioned target analytes. A paper disk integrated over the electrode area and loaded with the reagents required for the sample conditioning makes the analysis straightforward. The sensor thus produced can be inserted in a highly compact low-power instrument connected to a mobile phone, making an easy-to-use device suitable for on-site analytical studies. Graphical abstract: Image, graphical abstract